2003
DOI: 10.1080/16501970306125
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dynamic Lumbar Stabilization Exercise in Lumbar Microdiscectomy

Abstract: Dynamic lumbar stabilization exercises are an efficient and useful technique in the rehabilitation of patients who have undergone microdiscectomy. They relieve pain, improve functional parameters and strengthen trunk, abdominal and low back muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 21 publications
2
55
0
3
Order By: Relevance
“…Indications for lumbar disc surgery were extensive or unbearable pain radiating down to the lower extremity and/ or muscle weakness and, in majority of patients, a positive straight leg raising test gave a value of \60 [49,51]. Patients may also have presented loss of patellar or Achilles reflex, cauda equina syndrome and/or regional sensory loss.…”
Section: Methodsmentioning
confidence: 99%
“…Indications for lumbar disc surgery were extensive or unbearable pain radiating down to the lower extremity and/ or muscle weakness and, in majority of patients, a positive straight leg raising test gave a value of \60 [49,51]. Patients may also have presented loss of patellar or Achilles reflex, cauda equina syndrome and/or regional sensory loss.…”
Section: Methodsmentioning
confidence: 99%
“…In the Swedish spine register, based on 1,021 disc patients surgically treated during 2003, the corresponding mean levels of leg and back pain at 12-month follow-up were 23 and 26, respectively [46]. The excellent results of the homebased training group were unexpected and contrasting to previous studies, but in those, the control groups had a less active or no exercise programme, and compliance with the prescribed home training was not reported [4,15,52].…”
Section: Discussionmentioning
confidence: 80%
“…Johannsen et al [22] found these two treatment approaches almost equally effective regarding global health aspects, disability, pain and mobility. Yilmaz et al [52], however, found supervised dynamic lumbar stabilisation training to be more beneficial than home-based training, which in turn was more effective than no training. This is a pattern that has also been reported in other studies [4,15].…”
mentioning
confidence: 96%
See 2 more Smart Citations